JAKARTA-BANDUNG HIGH-SPEED TRAIN INFRASTRUCTURE DEVELOPMENT - Dedeh Maryani; Zainal Abidin (Institut Pemerintahan Dalam Negeri (IPDN), 2022)
In accelerating economic growth, Indonesia is actively implementing infrastructure development. One of the developments currently underway is the construction of the Jakarta-Bandung high-speed train infrastructure. Jakarta as the nation's capital and Bandung as the capital city of West Java Province as a buffer for the capital city have high mobility in the use of transportation means including trains. To support the business activities between the two cities, the government considers the development of high-speed train infrastructure as a priority development. Due to the limited Indonesian Budget, Indonesia decided to collaborate with the Chinese government in its development and financing. However, the implementation of the construction of the Jakarta-Bandung high-speed train infrastructure is not simple, because it involves various stakeholders, including the Central Government, the Chinese Government, the West Java Provincial Government, the Regency/City Governments that the high-speed train line passes, and the people. This study aims to describe the implementation of collaboration among all stakeholders. The research method used is qualitative descriptive. The results of this study indicate that there are still various technical obstacles faced so that the implementation of the Jakarta-Bandung high-speed train infrastructure development runs slowly. The right collaboration model found to be applicable in infrastructure development is the Transnational Model.